Will-To-Live Scale as a Predictor of Depressive Symptoms in Elderly: an Evidence-Based Case Report - Satryo, Eugene Alfathan; Qomarasandhi, Johan (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
An elderly man was admitted to inpatient care after a check-up with a gerontologist, stating that he had no will to continue living and showing other depressive symptoms. The gerontologist then ponders whether the will to live is prognostic for depression, specifically in elderly patients. The report aims to determine whether the will to live, measured by the Will-to-Live (WTL) scale, can predict depressive symptoms (DS) emerging in elderly patients. A literature search was conducted on three databases: PubMed, Cochrane, and EBSCOhost. Of the searches, two articles were selected for further critical appraisal using the criteria provided by the University of Oxford Centre of Evidence-Based Medicine. first study, using the WTL Scale to quantify WTL and the Geriatric Depression Scale (GDS) to measure DS, showed that WTL can predict DS but not vice versa with moderate negative correlation (r = -0.49 p<0.001). The second study analyzes the temporal relationship further, showing that WTL still has a negative correlation with DS (measured by modified GDS) (r=-0.4, p<0.05) when assessed in the same time frame but shows little to no correlation when used as a predictor for DS after a 1-year interval from the initial assessment (r= 0.14, p<0.05). The Will-To-Live Scale has the potential to be a more practical tool in predicting depressive symptoms in gerontology settings as compared to usual methods after further validation studies.